Digital resilience : is your company ready for the next cyber threat? - Rothrock, Ray A. (Gildan, 2018)
Cybercrime is on the rise--and businesses large and small are at risk. For management, the question is not if you will be targeted, but when. Are you prepared? Is your enterprise actively monitoring networks, taking steps to understand and contain attacks, enabling continued operation during an incident? Do you have a recovery plan ready?